2013
DOI: 10.1155/2013/420565
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Multiple Myeloma Coexisting with Primary Hyperparathyroidism and Review of the Literature

Abstract: Hypercalcemia is a common medical problem with an estimated prevalence of 15% among hospitalized patients. Multiple myeloma (MM) and primary hyperparathyroidism (PHPT) are among the most common causes of hypercalcemia but coexistence of both pathologic processes in a patient is an extremely rare phenomenon. In this paper we have discussed a patient presenting with this rare phenomenon. We have also provided a comprehensive review of the scientific literature published on codiagnosis of MM and PHPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 32 publications
2
15
0
1
Order By: Relevance
“…On the other hand, a prospective study done in 2002 showed the prevalence of monoclonal gammopathies is higher in patients with primary hyperparathyroidism when compared to the general population. That finding supports the hypothesis of an association between monoclonal gammopathy of undetermined significance or multiple myeloma with primary hyperparathyroidism [ 1 , 8 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…On the other hand, a prospective study done in 2002 showed the prevalence of monoclonal gammopathies is higher in patients with primary hyperparathyroidism when compared to the general population. That finding supports the hypothesis of an association between monoclonal gammopathy of undetermined significance or multiple myeloma with primary hyperparathyroidism [ 1 , 8 ].…”
Section: Discussionsupporting
confidence: 88%
“…Primary hyperparathyroidism can cause hypercalcemia through increasing calcium reabsorption by distal tubules in the kidneys, increasing bone resorption and increasing activation of vitamin D, which will increase gastrointestinal absorption of calcium [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…rülen ve sıklıkla atlanabilecek bir durumdur. Literatürde şu ana kadar yaklaşık 30 olguda PHP ve MM birlikteliği bildirilmiştir (2,3). Bu olguların bir kısmında öncelikle MM'ye bağlı olduğu düşünülen hiperkalsemi tedavi edilmeye çalışılmış, ancak hiperkalseminin kontrol altına alınamaması üzerine beraberinde PHP tanısının varlığı gösterilebilmiştir.…”
unclassified